A Review of Quality and Quantity of Foreign Students ' Education under the Characteristics of the Popularized Times - Rahman, Md Sahariar; Rahman, Md Shahanur; Quainoo, Eric Atta (International journal of social science and humanities research, 2021)
In recent years, the scale of international students in China is growing rapidly, but the quality of education for international students in China seems to be obviously lagging behind, which is reflected in the academic level. These disadvantages and deficiencies have seriously hindered the development of the education of foreign students in China. To improve the quality of international students in China, colleges and universities must carry out curriculum reform and strengthen the construction of teachers. The government and society must also play their respective roles in formulating long-term policies. It is expected to have a clear international education development strategy, establish the quality standards of education and teaching for international students in China, and establish the trinity of government, society and universities. Thus, the educational quality assurance system must be established to realize effective monitoring.